Socio-Cultural Aspects of Teaching Foreign Languages in The Faculty of Languages and Arts, State University of Jakarta (International Journal of Active Learning, 2018)
This study aims to identify the social and cultural aspects in the French and German textbooks. It stands to reason that learning a foreign language inevitably involves socio-cultural aspects as language does not stand alone but must be related to the context. When teachers teach foreign language at the same time they also introduce its socio-cultural aspects. In consequence, textbooks should contain all the socio-cultural aspects of the language to be learnt. CECRL, a theory derived from Didier, is employed to determine the socio-cultural aspects in the French and German textbooks. There are seven aspects of socio-cultural by Didier but the writers will only use six aspects, they are: La vie quotidienne, Les conditions de vie, les relations interpersonnelles, valeurs, croyences, et comportements, savoir-vivre, comportements rituels. The analysis of two textbooks show that the textbooks contain six aspects of socio- cultural having daily lives as the most dominant.